ANTHOLOGY OF THE GADDANG LITERATURE IN THE CITY OF CAUAYAN AND ITS IMPLICATION TO EDUCATION - Luna, Gabriel L. (International Journal of Psychosocial Rehabilitation, 2020)
Gaddang literature unfolds their way of life - aspirations, values and ideals, customs and traditions, beliefs, and way of doing things together. The collection of literature is essential part of the precious cultural heritage of the City of Cauayan. The study determined the anthology of the Gaddang literature with respect to folk songs, proverbs, riddles, poems, legends, and prayers. The literature defines who the Gaddang are; their identity, expressed in work, leisure activities, and frustrations as well as successes in life. The study used the descriptive ethnographic and documentary research; Interviews were conducted with the help of tape recorders, video tapes and field notes to gather the collections of the literature of the Gaddang.The research concluded that the Gaddang literature is an ethnic pride of the Gaddang indigenous community where they draw and formulate philosophy in life as expressed in their beliefs, customs and traditions, values and attitudes. The Gaddang literature provides readers especially the DepEd pupils vivid reflection of customs and beliefs as a people. The themes of the Gaddang songs, proverbs, riddles, poems and even epics are a reflection of indigenous people’s way of life, their emotions, sentiments, expressions, and love and life experiences. Most of the Gaddang literature speak of plentiful harvest, beauty of nature longings, fears of the heart, pains, prayers, frustrations, love and their way of living. The literature in the Gaddang ethnic communities at Cauayan City is an indigenous pride of the City that would help the Gaddang indigenous communities in their struggle or ethnic pride and cultural identity where the literary pieces contribute to the national